Supply Chain Risk Analysis in the Ready-to-Drink Beverage Industry Based on the Combination of SCOR and FMEA Methods - Berliana Adella Ananda; Hamidah Hendrarini; Mirza Andrian Syah (The University of Lampung, 2025)
The performance of the supply chain department requires precision and loyalty to vendors, which must, of course, align with established work procedures. The supply of raw materials that do not comply with the specified standards can lead to errors in the ongoing procedures. This study aims to identify risk priorities using the SCOR research method, analyze the sources of risk through the FMEA analysis method, and examine priority risks along with proposed strategies in the RTD (Ready-to-Drink) industry supply chain using a fishbone diagram supported by the 5W+1H model. Primary data was collected through direct observation at PT Great Giant Pineapple, interviews, and questionnaires distributed to 10 respondents with key roles in the RTD industry supply chain process. The findings of the study indicate that: (1) A total of 27 risks were identified in the RTD beverage industry supply chain, consisting of 9 risks in the planning process, 3 in sourcing, 8 in manufacturing, 4 in delivery, and 3 in returns; (2) There are three top-priority risks with the highest rankings; (3) The proposed strategies are predominantly focused on improving the work systems of vendors and the purchasing department to prevent recurrence in future periods